Immune Reconstitution-Based Score for Risk Stratification of Chronic Graft-Versus-Host Disease Patients - Serpenti, Fabio; Lorentino, Francesca; Marktel, Sarah; Milani, Raffaella; Messina, Carlo; Greco, Raffaella; Girlanda, Stefania; Clerici, Daniela; Giglio, Fabio; Liberatore, Carmine; Farina, Francesca; Mastaglio, Sara; et al. (Frontiers in Oncology, 2021)
Introduction Allogeneic stem cell transplantation survivors are at a relevant risk of developing chronic GvHD (cGvHD), which importantly affects quality-of-life and increases morbidity and mortality. Early identification of patients at risk of cGvHD related morbidity could represent a relevant tool to tailor preventive strategies. Aim of this study was to evaluate the prognostic power of immune-reconstitution (IR) at cGvHD onset through a IR-based score. Methods We analyzed data from 411 adult patients consecutively transplanted between January 2011 and December 2016 at our Institution: 151 patients developed cGvHD (median follow-up 4 years). A first set of 111 consecutive patients with cGvHD entered the test cohort while additional consecutive 40 pts represented the validation cohort. A Cox multivariate models for OS (overall survival) in patients with cGvHD of any severity allowed the identification of 6 variables independently predicting OS and TRM (transplant related mortality). A formula for a prognostic risk index by using the β coefficients derived from the model was designed. Each patient was assigned a score defining 3 groups of risk (low, intermediate and high). Results Our multivariate model defined the variables independently predicting OS at cGvHD onset: CD4+>233/mcl, NK<115/mcl, IgA<0.43g/L, IgM<0.45g/L, Karnofsky PS<80%, Platelets<100.000/μL. Low-risk patients were defined as having a score ≤3.09, intermediate-risk >3.09 and ≤6.9, high-risk >6.9. By ROC analysis, we identified a cut-off of 6.310 for both TRM and overall mortality. In the test cohort the 3y OS and TRM from cGvHD occurrence were 100% and 0 for low-risk patients, 78% (95%CI, 59-89) and 12% (95%CI, 4-26) for intermediate-risk, 37% (95%CI, 15-58) and 27% (95%CI, 8-49) for high-risk (OS p<0.001; TRM p0.04). The validation cohort confirmed the model with 3y OS and TRM of 92% (95%CI, 57-99%) and 8% (95%CI, 1-30%) for low-risk patients, 75% (95%CI, 41-91%) and 25% (95%CI, 6-52%) for intermediate risk, 53% (95%CI, 26-74%) and 35% (95%CI, 12-59%) for high-risk. Conclusions IR-score at diagnosis of cGvHD predicts GvHD severity and overall-survival. IR score may contribute to the risk stratification of patients: we propose to adopt the IR-score to identify patients at high-risk and modulate cGvHD treatments accordingly in the context of clinical trial.